2011
DOI: 10.1159/000330579
|View full text |Cite
|
Sign up to set email alerts
|

Power of Data Mining Methods to Detect Genetic Associations and Interactions

Abstract: Background: Genetic association studies, thus far, have focused on the analysis of individual main effects of SNP markers. Nonetheless, there is a clear need for modeling epistasis or gene-gene interactions to better understand the biologic basis of existing associations. Tree-based methods have been widely studied as tools for building prediction models based on complex variable interactions. An understanding of the power of such methods for the discovery of genetic associations in the presence of complex int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…This good performance is documented in several independent comparison studies implementing different simulation settings [26,54,73,17]. In these studies, however, standard VIMs (either Gini or permutation) are used to rank the SNPs.…”
Section: Predictors Involved In Interactionsmentioning
confidence: 87%
“…This good performance is documented in several independent comparison studies implementing different simulation settings [26,54,73,17]. In these studies, however, standard VIMs (either Gini or permutation) are used to rank the SNPs.…”
Section: Predictors Involved In Interactionsmentioning
confidence: 87%
“…Variable importance rankings were also derived within the R randomForest procedure using the Breiman–Cutler permutation strategy (Breiman and Cutler, 2001), which has good performance and comparative efficacy (Molinaro et al ., 2011). This procedure estimates, for each variable, the degree to which random permutation of its values decreases prediction accuracy of the machine, while retaining original values of all other variables.…”
Section: Methodsmentioning
confidence: 99%
“…The power of the variable importance measure to discriminate between relevant and non-relevant variables was poor, too. The approach of Altmann et al (2010), which showed high power in other studies (Molinaro et al;2011;Hapfelmeier and Ulm;, also had very low statistical power in our studies. This discrepancy is likely related to the fact that the existing studies included only a few variables, while our studies are based on several thousands of variables.…”
Section: Discussionmentioning
confidence: 52%